Interação entre os ciclones extratropicais do hemisfério sul e os gelos marinhos no mar de Weddell - Britto, Italo Venceslau (Universidade Federal do Rio Grande do Norte, 2017)
Extratropical cyclones present characteristics that affect the entire climate in the southern hemisphere, from its formation to its dissipation, being this system, the study's goal since the 19th century. Sea ice is of fundamental importance to the global climate system, since its physical properties influence the exchange between ocean and atmosphere. Therefore, the main objective of this work was to analyze the interactions between extratropical cyclones and the extreme variability of sea ice in the Southern Hemisphere between 1979 and 2016. Data were used at the Sea Level Medium Pressure (PNMM) with spatial resolution of 0.75° x 0.75° of grid point, with time resolution of 6 hours, extracted from the European Center for Medium-Range Weather Forecasts (ECMWF) reanalysis, for the same period. In addition to the PNMM, data from the geopotential height at 500 hPa, zonal and southern wind at the levels of 1000, 850 and 500 hPa, as well as relative humidity were also used, and also at 1000, 850 and 500 hPa levels. Sea ice extent data were obtained from the University of Colorado's National Snow and Ice Data Center (NSIDC), and the sea ice concentration is derived from the Scanning Multichannel Microwave Radiometer (SMMR) sensors aboard the Nimbus-7 satellite , and the Special Sensor Microwave / Imager (SSM / I), aboard the Defense Meteorological Satellite Program. The results showed that in the austral summer, the thermodynamic regions more favorable to the formation of extratropical cyclones are mainly found in the average latitudes, whereas in the austral winter there was an amplification of these areas, and that in the seas of Weddell and Ross were verified more positive anomalies of the concentration of sea ice and more cyclogenesis. Keywords: atmosphere, sea ice, interaction. Os ciclones extratropicais apresentam características que afetam todo o clima no hemisfério sul, desde sua formação até sua dissipação, sendo este sistema, alvo de estudo pelos cientistas desde o século XIX. O gelo marinho é de ...